2019
DOI: 10.21273/hortsci13569-18
|View full text |Cite
|
Sign up to set email alerts
|

Organic Acids Exuded From Roots Increase the Available Potassium Content in the Rhizosphere Soil: A Rhizobag Experiment in Nicotiana tabacum

Abstract: Additional index words. root, soil potassium, organic acid, root vigor, stress-resistant enzyme activity Abstract. Organic acid secretion from higher plant roots into the rhizosphere soil plays an important role in nutrient acquisition and metal detoxification; however, their precise functions and the related mechanisms in abiotic stress tolerance remain poorly understood. Tobacco is an important crop plant, so thoroughly elucidating these factors in tobacco is of high priority. In the present study, the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The soil macronutrient like available nitrogen (N), Phosphorous (P), Potassium (K), and zinc (Zn) micronutrient contents were also increased in the rhizosphere soil of plants treated with ZnONPs. The increased soil available K, P and Zn contents in the rhizosphere soil may be attributed to enhanced root growth, higher production of the organic acids by the plant roots [41] and occurrence of P-solubilizing microbes [42] as indicated through greater alkaline and acid phosphatase activities which cumulatively led to decrease in the pH in near vicinity of the growing roots thus facilitating improved soil available K, P and Zn contents. The enhancement in the soil N content in plants treated with ZnONPs must be due to enhanced microbial biomass or activity particularly the non-symbiotic N-fixer populations [43,44] which were increased due to seed priming and coating treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The soil macronutrient like available nitrogen (N), Phosphorous (P), Potassium (K), and zinc (Zn) micronutrient contents were also increased in the rhizosphere soil of plants treated with ZnONPs. The increased soil available K, P and Zn contents in the rhizosphere soil may be attributed to enhanced root growth, higher production of the organic acids by the plant roots [41] and occurrence of P-solubilizing microbes [42] as indicated through greater alkaline and acid phosphatase activities which cumulatively led to decrease in the pH in near vicinity of the growing roots thus facilitating improved soil available K, P and Zn contents. The enhancement in the soil N content in plants treated with ZnONPs must be due to enhanced microbial biomass or activity particularly the non-symbiotic N-fixer populations [43,44] which were increased due to seed priming and coating treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Further, plants can improve their capacity for K + uptake by mycorrhization [ 212 , 213 , 214 ] and root exudates [ 215 , 216 ]. Some studies have suggested that plants can invest C in root exudates [ 215 , 216 ] or in root mycorrhization [ 217 , 218 , 219 ], specifically to cope with K + soil limitation. However, other studies have not observed a mycorrhization rise related to plant K + limitation.…”
Section: Role Of K In Terrestrial Ecosystemsmentioning
confidence: 99%
“…Flue-cured tobacco is a special type of cash crop, and its root exudates have large effects on soil characteristics (Li et al 2017). Flue-cured tobacco root exudates can increase the content of available nutrients in soil, significantly affect the activities of phytases, catalase, and polyphenol oxidase (Lung et al 2008;Yang et al 2019). In addition, organic acids in fluecured tobacco root exudates can participate in plant growth regulation as chemical attractants to stimulate microbial growth (Faure et al 2009;Fang et al 2016).…”
Section: Introductionmentioning
confidence: 99%